New Digital Forensics Investigation Process (NDFIP) - Oğuz, Ramazan; Eryigit, Recep (Fırat University, 2024)
This study aims to develop the New Digital Forensics Investigation Process (YABIS) in response to the increasing complexity of digital forensics investigations. A comparative analysis of existing digital forensics processes at both national and international levels has been conducted to design a comprehensive and legally compliant process. YABIS offers an extensive approach that includes critical stages such as preparation and the return of evidence, which are often overlooked. This process has the potential to enhance the efficiency of digital forensic investigations, preserve the integrity of evidence, and ensure the reliable use of digital evidence in legal proceedings. The research emphasizes the importance of digital forensics experts, law enforcement, and other relevant parties meticulously implementing each stage of the process and continuously improving it. Through this approach, more successful and effective strategies can be developed in the fight against digital crimes.

Bu çalışmanın amacı, adli bilişim incelemelerinin giderek artan karmaşıklığına çözüm sunmak amacıyla “Yeni Adli Bilişim İnceleme Süreci (YABİS)” geliştirmeyi hedeflemektedir. Ulusal ve uluslararası düzeyde mevcut adli bilişim süreçlerinin karşılaştırmalı analizi yapılarak, hukuki gerekliliklere uygun, eksiksiz ve kapsamlı bir süreç tasarlanmıştır. YABİS, hazırlık ve delillerin iadesi gibi genellikle göz ardı edilen kritik aşamaları içerecek şekilde kapsamlı bir yaklaşım sunmaktadır. Bu süreç, adli bilişim incelemelerinin etkinliğini artırma, delillerin bütünlüğünü koruma ve dijital kanıtların adli süreçlerde daha güvenilir bir şekilde kullanılmasını sağlama potansiyeline sahiptir. Araştırma, adli bilişim uzmanları, kolluk kuvvetleri ve ilgili diğer tarafların sürecin her aşamasını dikkatlice uygulaması ve sürekli olarak geliştirilmesinin önemini vurgulamaktadır. Bu yaklaşım sayesinde, dijital suçlarla mücadelede daha başarılı ve etkili stratejiler geliştirilebilir.
Yeni Adli Bilişim İnceleme Süreci (YABİS)
Keywords: Computer Forensics; Adli Bilişim